Morphological Characterization and Optical Properties of CIGS/TiO2 Thin Films Using Sputtering Technique - Hayati, SB. Widia Rezaly Biharu; Erdiansyah, Erdiansyah; Hendrawan, Win (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2024)
Solar energy as a renewable energy source, is currently an important alternative to meet energy needs because of its unlimited amount and environmentally friendly. Almost the entire surface of the earth receives sunlight optimally, so breakthroughs are needed to transform the solar energy into electricity. In the research development process that was to develop advanced materials to support the development of alternative energy. Thin film synthesis was carried out using the Physical Vapor Deposition (PVD) of Direct Current (DC) Sputtering method on Indium Tin Oxide (ITO) substrates using Copper Indium Gallium Selenide (CIGS) and TiO2 with deposition time variations of 30, 45, and 60 minutes. Based on the test results, thin film surface with the largest grain size is 266.75 nm at CIGS/TiO2 45 minutes. This shows that more CIGS and TiO2 atoms are released from the target surface, forming clumps that cover the substrate surface along with the addition of deposition time. The longer the deposition time shows the higher the absorbance value. The highest absorbance value is 4.60873, which was achieved by 60 minutes CIGS/TiO2 sample with wavelength of 271 nm.